ANATOMY OF THE BACK MUSCLES - Kattaxodjayeva Dinara Utkurxodjayevna (Western European Studies, 2025)
The work examines the anatomy of the back muscles, which are divided into superficial and deep. The back area, occipital parts of the neck and the contour of the shoulder blades are studied. It is shown that the trapezius muscle has the shape of a triangle, the latissimus dorsi is flat, the small rhomboid muscle has a connective tissue layer, and the muscle that lifts the scapula is rotator.
Keywords: anatomy; muscles; back; shape